Calcium Metabolism, Immunity and Reproduction in Early Postpartum Dairy Cows - Szilvia Kusza; Zoltán Bagi; Putri Kusuma Astuti; George Wanjala; Ottó Szenci; Árpád Csaba Bajcsy (Animals)
Vitamin D is essential for calcium homeostasis, bone mineralization, immunity, and disease prevention. In a field study with Holstein-Friesian dairy cows, the impact of prepartum vitamin D3 treatment on early postpartum placental gene expression, focusing on calcium metabolism, feto-placental growth, and immune response, had been investigated. Eight multiparous cows were treated with 10 mL vitamin D3 (1 million IU cholecalciferol/mL) intramuscularly on day 273 of pregnancy, while eight others remained untreated and served as controls. Placental tissues were collected post-calving, and gene expression was analyzed using quantitative real-time PCR. Among 23 genes, 5 showed significant downregulation in the treated group: CaBP-9k (reduced by 88.1% from 32.80 ± 91.50 to 3.90 ± 8.54), ESR1 (reduced by 95.7% from 7.89 ± 17.87 to 0.34 ± 0.34), LHR (reduced by 96.5% from 3.75 ± 5.45 to 0.13 ± 0.17), NOD1 (reduced by 94.1% from 4.21 ± 7.00 to 0.25 ± 0.30), and TLR1 (reduced by 99.7% from 24.80 ± 61.45 to 0.07 ± 0.08). These results suggest that vitamin D3 supplementation affects key pathways related to calcium transport, reproductive function, and immune response in the bovine placenta. These molecular changes may help to explain improved calcium homeostasis and reduced postpartum complications, offering insights into how targeted nutritional interventions can enhance reproductive efficiency in high-producing dairy cows.